Transcriptome composition of the preoptic area in mid-age and escitalopram treatment in male mice. (27th May 2016) - Moriya, Shogo; Soga, Tomoko; Wong, Dutt Way; Parhar, Ishwar S.
Highlights: Age-related genes in the POA were isolated. Genes affected by escitalopram treatment in the POA were isolated. Transcriptomes between mid-age and escitalopram treatment were compared. Abstract: The decrease in serotonergic neurotransmission during aging can increase the risk of neuropsychiatric diseases such as depression in elderly population and decline the reproductive system. Therefore, it is important to understand the age-associated molecular mechanisms of brain aging. In this study, the effect of aging and chronic escitalopram (antidepressant) treatment to admit mice was investigated by comparing transcriptomes in the preoptic area (POA) which is a key nucleus for reproduction. In the mid-aged brain, the immune system-related genes were increased and hormone response-related genes were decreased. In the escitalopram treated brains, transcription-, granule cell proliferation- and vasoconstriction-related genes were increased and olfactory receptors were decreased. Since homeostasis and neuroprotection-related genes were altered in both of mid-age and escitalopram treatment, these genes could be important for serotonin related physiologies in the POA.